A novel Killian–Jamieson diverticulectomy using a thyroid gland flap: a case report - Takuya Saito; Tetsuya Ogawa; Shintaro Kurahashi; Hiroki Okamoto; Hirotake Gonda; Tatsuki Matsumura; Takaaki Osawa; Yasuyuki Fukami; Shunichiro Komatsu; Kenitiro Kaneko; Tsuyoshi Sano (Surgical Case Reports)
Abstract Background A Killian–Jamieson diverticulum is a rare pharyngoesophageal diverticulum that is radically treated by diverticulectomy. However, there is no consensus on whether cricopharyngeal myotomy is necessary, and the optimal surgical methods that prevent postoperative complications such as leakage are undetermined. Case presentation A 49-year-old man was referred to our hospital with oropharyngeal dysphagia while eating. The patient was preoperatively diagnosed with a Killian–Jamieson diverticulum based on radiographic and clinical findings and underwent a transcervical diverticulectomy. The recurrent laryngeal nerves were preserved using an intraoperative nerve monitoring system, and the diverticulum was identified without difficulty. A partial cricopharyngeal myotomy was performed to expose the base of the diverticulum. The diverticulum was transected transversally using a linear stapler under the guidance of intraoperative upper intestinal endoscopy. A thyroid gland flap supplied by the superior thyroid artery was harvested and placed overlapping the area of the partial cricopharyngeal myotomy. Due to the proximity of the recurrent laryngeal nerve course to the diverticulum stump, the staple line was not buried with sutures. The thyroid gland flap with its rich vascular supply was fixed to completely cover the staple line on the cut surface of the thyroid gland. The postoperative course was uneventful, without vocal cord paralysis. The patient was discharged on postoperative day 8. He developed no clinical signs suggesting leakage, recurrence, or adverse events. Conclusion Killian–Jamieson diverticulectomy using a thyroid gland flap and partial cricopharyngeal myotomy is a valid treatment option that may prevent complications and recurrence. Precise evaluation of the diverticulum using an intraoperative nerve monitoring system is crucial for the repair.